The Yangshan Deepwater Port: the largest port for deepwater and river terminals ever designed (Research, Society and Development, 2020)
China would never become the largest exporter in the world without its ports, and none of them portrays the exponential growth in the country's infrastructure as well as the Yangshan Port. The mega-structure helped Shanghai to overtake Singapore in the ranking of cities with the highest cargo handling in the world and set historical records of flow with more than 25 million containers in one year. A huge ally to efficient waterway handling is the huge Yangtze River, which flows through much of East China. Billions of dollars worth of goods sail the channel every year to be transported around the world. However, with the evolution of the size of the vessels and the deficiency in the depth of the river, China found the perfect solution, the design of the largest port terminal in deep and fluvial waters. This work aims to present the port of Yangshan, show its importance in the context of international transport and the characteristics that make it one of the most efficient and promising ports in the world.